The Evening Complex and the Chromatin-Remodeling Factor PICKLE Coordinately Control Seed Dormancy by Directly Repressing DOG1 in Arabidopsis - Zha, Ping (Plant Commun, 2019)
Primary seed dormancy is acquired during seed development and maturation, which is important for plant fitness and survival. DELAY OF GERMINATION1 (DOG1) plays a critical role in inducing seed dormancy. DOG1 expression increases rapidly during seed development, but the precise mechanism underlying this process remains elusive. In this study, we showed that mutants with a loss or reduced function of the chromatin-remodeling factor PICKLE (PKL) exhibit increased seed dormancy. PKL associates with DOG1 chromatin and inhibits its transcription. We found that PKL physically interacts with LUX ARRHYTHMO (LUX), a member of the evening complex (EC) of the circadian clock. Furthermore, LUX directly binds to a specific coding sequence of DOG1, and DOG1 acts genetically downstream of PKL and LUX. Mutations in either LUX or EARLY FLOWERING3 (ELF3) encoding another member of the EC led to increased DOG1 expression and enhanced seed dormancy. Surprisingly, these phenotypes were abolished when the parent plants were grown under continuous light. In addition, we observed that loss of function of either PKL or LUX decreased H3K27me3 levels at the DOG1 locus. Taken together, our study reveals a regulatory mechanism in which EC proteins coordinate with PKL to transmit circadian signals for directly regulating DOG1 expression and seed dormancy during seed development.